The Effect of Regional Fiscal Independence on Development Expenditure - ramadhani, muhammad harits zidni khatib; Rahmah, Asmadhini Handayani; Fitria, Yunita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
T This study examines the effect of regional fiscal independence on development expenditure in Indonesian local governments, focusing on regencies and municipalities. Fiscal independence is measured by the share of local own-source revenue (Pendapatan Asli Daerah, PAD) in total regional revenue, reflecting the degree of fiscal autonomy. Development expenditure is proxied by capital expenditure, representing long-term public investment in infrastructure and productive assets. The study uses panel data from 35 regencies and municipalities over the 2018–2022 period, yielding 175 observations. A fixed effects panel regression model is employed, selected through Chow and Hausman tests, to control for unobserved time-invariant regional characteristics, including institutional capacity and governance quality. The results indicate that regional fiscal independence has a positive and statistically significant effect on capital expenditure. Greater fiscal independence is associated with higher development spending, suggesting that increased reliance on own-source revenue strengthens local governments’ ability to finance development-oriented investments. In addition, both local own-source revenue and central government transfers have positive and significant effects on capital expenditure, although intergovernmental transfers remain the primary funding source. In contrast, regional gross domestic product does not show a significant influence on development expenditure after controlling for fiscal variables.These findings imply that while fiscal independence expands local fiscal space, development expenditure in Indonesia remains highly dependent on central government transfers. Strengthening local revenue capacity is therefore essential to enhancing fiscal autonomy, reducing transfer dependency, and supporting more sustainable regional development within the fiscal decentralization framework.